An operator-based approach for the construction of closed-form solutions to fractional differential equations - Navickas, Zenonas; Telksnys, Tadas; Timofejeva, Inga; Marcinkevičius, Romas; Ragulskis, Minvydas (Mathematical Modelling and Analysis, 2018)
An operator-based approach for the construction of closed-form solutions to fractional differential equations is presented in this paper. The technique is based on the analysis of Caputo and Riemann-Liouville algebras of fractional power series. Explicit solutions to a class of linear fractional differential equations are obtained in terms of Mittag-Leffler and fractionally-integrated exponential functions in order to demonstrate the viability of the proposed technique.